2009
DOI: 10.1158/1078-0432.ccr-09-0645
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node–Targeted Immunotherapy Mediates Potent Immunity Resulting in Regression of Isolated or Metastatic Human Papillomavirus–Transformed Tumors

Abstract: Purpose: The goal of this study was to investigate the therapeutic potential of a novel immunotherapy strategy resulting in immunity to localized or metastatic human papillomavirus 16-transformed murine tumors. Experimental Design: Animals bearing E7-expressing tumors were coimmunized by lymph node injection with E7 49-57 antigen and TLR3-ligand (synthetic dsRNA). Immune responses were measured by flow cytometry and antitumor efficacy was evaluated by tumor size and survival. In situ cytotoxicity assays and id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…4B) induced by targeting the vaccine to the tdLN led to regression of early-stage tumors and more impressively of tumors having reached the Swiss legal limit of 1 cm 3 . In the literature, cancer vaccines are usually administered when the tumors are 5 to 7 mm in diameter or even before they are detectable, and also do not usually induce this high number of TAA-specific CD8 þ T cells in the blood and the LNs (17,19,30,38,44), thus emphasizing the benefits of nanoparticle-mediated targeting of antigen and adjuvant to DCs in the tdLN (18,38,45). We noted, however, that after regressing some tumors grew back.…”
Section: Discussionmentioning
confidence: 79%
“…4B) induced by targeting the vaccine to the tdLN led to regression of early-stage tumors and more impressively of tumors having reached the Swiss legal limit of 1 cm 3 . In the literature, cancer vaccines are usually administered when the tumors are 5 to 7 mm in diameter or even before they are detectable, and also do not usually induce this high number of TAA-specific CD8 þ T cells in the blood and the LNs (17,19,30,38,44), thus emphasizing the benefits of nanoparticle-mediated targeting of antigen and adjuvant to DCs in the tdLN (18,38,45). We noted, however, that after regressing some tumors grew back.…”
Section: Discussionmentioning
confidence: 79%
“…27 In addition, substantial immune responses achieved through intra-lymph node immunization with peptide and a TLR agonist were a prerequisite for effective control of tumor progression in immune-competent mice. 30 Therefore, we hypothesized that intra-lymph node DNA vaccination is an optimal priming strategy with the caveat that it is still not known whether a preferential induction of a specialized T-cell subset or simply a large expansion of TAA-specific T cells is crucial for the effectiveness of this category of vaccine. In addition, it has been reported that TLR agonists can activate TLR signaling and B7-H1 (PD-L1) expression on tumor cells resulting in T-cell suppression, 31,32 although systemic exposure to TLR agonists is expected to be limited after intra-lymph node injection (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis suggested by the authors is that HPV-16-positive tumors have increased antigenicity through the E7 antigen, causing enhanced stimulation of the immune system, which more readily identifies tumor cells as foreign. This hypothesis is supported by a study led by Smith et al, in which the intralymphatic immunization of mice bearing E7-expressing tumors with E7 peptide resulted in a considerable expansion of E7-specific CD8 cells, which are effective in suppressing disease progression (Smith et al, 2009). In another animal model, the DNA vaccine with HSP70 fused to HPV-16 E7 has been demonstrated to dramatically increase the frequency of E7-specific CD8-positive T cells and to enhance the antitumor effects against E7-expressing tumor cells (Chen et al, 2000).…”
Section: Effects Of Hpv On the Immune System Of Patients With Benign mentioning
confidence: 78%